Analisis Kesesuaian Prosedur Konfirmasi Eksternal dalam Audit Piutang dengan Standar Audit 505 Studi Kasus Pada KAP X - Putri, Dian Oktaviana; Widoretno, Astrini Aning (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the compatibility between the application of confirmation used by KAP X auditors in conducting receivables audits, with Audit Standard (SA) 505 on External Confirmation issued by the Indonesian Institute of Public Accountants (IAPI). This study uses a qualitative research method, where the researcher observes how the auditor of KAP X carries out external confirmation procedures to ensure the correctness of the value of the company's receivables balance. The data collection techniques used in this study were participatory observation and interviews. The data obtained in this study will be analyzed using qualitative methods. The results of this study state that the external confirmation procedure carried out by the KAP X auditor is in accordance with the external confirmation provisions contained in the Audit Standard (SA) 505 published by the Indonesian Institute of Public Accountants (IAPI). The implication of this study is the need for auditors to evaluate the sampling results of the company's receivables data in order to be able to improve the efficiency and effectiveness of the external confirmation procedures implemented.